Magna Latrocinia di Era Modern: Sintesis Etika Politik Basilius Agung dan Agustinus sebagai Fondasi Moral untuk Reformasi Etos Pejabat Publik di Indonesia - Hendi; Sugianto (Reformed Center for Religion and Society, 2026)
The crisis of public trust in Indonesia, driven by systemic corruption, signifies a fundamental ethical problem among public officials. Contemporary reform approaches (institutional, socio-cultural, and behavioral) tend to be secular-rationalistic and fail to address the teleological question of power's ultimate purpose. To fill this moral-foundational gap, this research turns to Patristic political ethics. Using a qualitative literature study method, this article analyzes the concepts of oikonomia (stewardship) from Basil the Great and iustitia (justice) from Augustine of Hippo. The analysis reveals that Basil's oikonomia redefines public office as stewardship for the poor, while Augustine's iustitia establishes moral justice as the condition for state legitimacy. A synthesis of both yields a theo-ethical framework that reforms the ethos of public officials by reorienting the purpose of office from power to service and motivation from self-love to a love for justice. This study concludes that the Basilian-Augustinian framework offers a virtue-ethics foundation that complements existing reforms, shifting the focus from merely a